Juridical Analysis of the Role of the Regional Supervisory Council towards Notaries Who Make Mistakes in Making Deeds - H M Soerya Respationo; Markus Gunawan; Jose Natanael Kusnadi Putra (Journal of Education Technology Information Social Sciences and Health, 2024)
A notary is a public official who has the authority to make authentic deeds and has other authorities as intended in this Law or based on other laws. This research uses a normative juridical legal method with an empirical sociological approach. Data was obtained through analysis of legal documents and through an interview process directly with members of the regional supervisory board. The aim of this research is to determine the duties and functions of the regional supervisory council in carrying out supervision, inspection and imposing sanctions on notaries. The problem discussed in this research is the duties and functions of Notaries as community servants carrying out some of the duties of the State and therefore it is very important for notaries in holding their positions to provide services to the community and in the interests of the community. This research method uses qualitative methods with data obtained through in-depth interviews with members of the Regional Supervisory Council with detailed comprehensive observations carried out. The results of this research state that the Notary Supervisory Council can carry out its duties and functions in a tiered or non-tiered manner. In relation to the imposition of sanctions, examinations are carried out in stages, starting from the Regional Supervisory Council, Regional Supervisory Council and Central Supervisory Council. However, the imposition of sanctions in the form of verbal or written warnings is the final authority of the Regional Supervisory Council, and the imposition of sanctions in the form of dismissal is the final authority of the Regional Supervisory Council. the authority of the Central Supervisory Council, and the Minister of Law and Human Rights of the Republic of Indonesia who will issue a Decree on dismissal.